2007
DOI: 10.1007/s10508-007-9208-x
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Visual Attention to Erotic and Non-Erotic Stimuli

Abstract: It has been suggested that sex differences in the processing of erotic material (e.g., memory, genital arousal, brain activation patterns) may also be reflected by differential attention to visual cues in erotic material. To test this hypothesis, we presented 20 heterosexual men and 20 heterosexual women with erotic and non-erotic images of heterosexual couples and tracked their eye movements during scene presentation. Results supported previous findings that erotic and non-erotic information was visually proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
124
4
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(152 citation statements)
references
References 33 publications
22
124
4
2
Order By: Relevance
“…Men viewed female pictures significantly longer than they did male pictures, whereas women tended to split their attention more evenly between pictures of the two genders. This finding supports those of previous studies but also extends those findings to a Chinese sample for the first time, and provides much needed cross-cultural replication (e.g., Ebsworth & Lalumiere, 2012;Israel & Strassberg, 2009;Lykins et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Men viewed female pictures significantly longer than they did male pictures, whereas women tended to split their attention more evenly between pictures of the two genders. This finding supports those of previous studies but also extends those findings to a Chinese sample for the first time, and provides much needed cross-cultural replication (e.g., Ebsworth & Lalumiere, 2012;Israel & Strassberg, 2009;Lykins et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Studies using eye-tracking techniques also show that heterosexual men are more gender-specific in sexual interest than heterosexual women in measures of fixation duration and count (Lykins, Meana, & Strauss, 2008). One recent study using eye tracking reported that heterosexual men oriented more rapidly to female than male targets, while heterosexual women oriented at similar speeds to male and female targets.…”
Section: Introductionmentioning
confidence: 99%
“…First, if identifiable stimuli from the IAPS or the Affective Norms for English Words (ANEW; Bradley & Lang, 1999) databases were used, we retrieved their normative valence and arousal ratings from their original databases. Second, for studies using smiling faces expressing happiness from the NimStim (Tottenham et al, 2009), the Karolinska Directed Emotional Faces (KDEF; Lundqvist, Flykt, & Öhman, 1997) and the Picture of Facial Affect (PFA; Ekman & Friesen, 1976) databases we coded their valence and arousal based on their respective studies investigating the arousal and valence dimensions of these stimuli (Adolph & Alpers, 2010;Johnsen, Thayer, & Hugdahl, 1995).…”
Section: Coding System and Coding Decisionsmentioning
confidence: 99%
“…This view has been further supported by women's preference for viewing other female bodies. For instance, when presented with erotic and non-erotic images of heterosexual couples, men looked at female bodies significantly longer than male bodies in the picture, whereas women tended to distribute their attention evenly between female and male bodies (Lykins, Meana, & Strauss, 2008). Similarly, when inspecting sexually explicit photos, the amount of viewing time directed at female bodies was indistinguishable between male and female viewers (Rupp & Wallen, 2007).…”
Section: Introductionmentioning
confidence: 96%